Coronal-Radicular and Periodontal Complications in Cases of Teeth with Endodontic Treatments in Medical Records - Adriana Pirte; Andrea Zatyko; P. Lajosi; Alina Venter; Mariana Muresan (Romanian Society of Oral Rehabilitation, 2010)
INTRODUCTION: to present the bring to attention the coronal - radicular and periodontal changes that might occur in time, at the level of teeth that, have suffered an endodontic treatment in their medical history. At the same time, some accidents have been monitored, that are likely to occur during endodontic treatment. MATERIAL AND METHOD: In order to follow these dental-periodontal changes a retrospective study has been performed. A number of 470 retrovalveolar, isometric and ortoradial radiographies have been analyzed. Teeth on these radigraphies have been divided into two groups. RESULTS: After analyzing the qualities of radicular obturations we have obtained the following results: correct 46%, incomplete 37%, with trans-passing 6%, false path 1%, un-obturated 5%. After analyzing those results by teeth groups, the highest rate of correct obturations that we have discovered was in case of the frontal group (55%), and the highest rate of incomplete obturations in cases of molars (40%). The aspect of apical periodont in cases of teeth with endodontic treatment was as follows: 65% with no changes, 24,5% periodical granuloma , 9,5% a slight widening of the periodical space and 1% radicular cyst. CONCLUSIONS: The incidence of cases when teeth with endodontic treatment that require a new endodontic intervention is quite increased.